Pengembangan Bisnis Pariwisata Kebun Raya Bogor Pada Masa Pandemik Covid 19 Berdasarkan Daya Dukung Wisata dan CHSE - Susilowati, Rosento, Isnurrini Hidayat (RJABM (Research Journal of Accounting and Business Management), 2022)
The impact of the COVID-19 pandemic caused tourist visits to decline sharply which led to a decline in regional income and foreign exchange from the tourism sector. Nowadays people have new habits where in determining choices or tourist destinations they consider health, security and safety factors. Opening and redeveloping the tourism sector, the Ministry of Tourism and Creative Economy is preparing a Cleanliness, Health, Safety and Environmental Sustainable (CHSE) program with its carrying capacity. This is also done by the Bogor Botanical Gardens tourist attraction. This study aims to explore internal and external factors in the business development of the tourism sector based on the carrying capacity of tourism and CHSE in the Bogor Botanical Gardens, followed by formulating alternative strategies and priority strategies using SWOT analysis. The study used a qualitative descriptive method. Based on the strategic analysis of the development of the Bogor Botanical Gardens tourism object, it is in quadrant I between external opportunities and internal strengths with management strategies by implementing CHSE, adding facilities and infrastructure to support CHSE, for example ticket purchases are made in two events, namely online and offline applications and additional toilet facilities. The next strategy is to add educational tourism spots for ornamental plant maintenance to visitors and actively post activities on Instagram and create an attractive website.Keywords: SWOT, Tourism Business Development